Русский дом: настольная книга хозяйки / [составители: А. А. Халин, Н. С. Сунин] - Халин А. А. (Нижний Новгород, 1991)
Экземпляры: аб. (1992) / Инвентарный номер: 35488 / Цена: / Сис.шифр: 37.279 / Авт.знак: Р 89 / ГРНТИ: 75.35 / ББК: 37.279